The techno-legal dynamics of cyber crimes in Industry 5.0 - Kaur, Gagandeep; Choudhury, Tanupriya; Balamurugan, S. (Industry 5.0 transformation applications., 2025)
This book explores the core principles, technological advancements, and legal challenges of Industry 5.0's digital transformation. Industry 5.0 has enhanced the operational efficiency of the entire manufacturing process by incorporating multiple emerging technologies; however, high-tech cybercrimes have prompted legal scholars worldwide to rethink the fundamental principles of technology and law. The Techno-Legal Dynamics of Cyber Crimes in Industry 5.0 shows how advanced technologies, such as artificial intelligence, the Internet of Things, and robotics, are integrated within manufacturing environments. It explores the intricate relationship between legal systems and technological advancements and addresses the rise of cybercrime following Industry 5.0's digital transformation. Focusing on the interaction between technology and law, the book investigates current cyberlaw issues and solutions. It draws insights from diverse experts, including scholars, legal professionals, and industry leaders, emphasizing effective regulations to minimize cyber threat risks for Industry 5.0. By adopting an international viewpoint, this book sheds light on various dimensions of nascent cybercrimes and legislative efforts worldwide aimed at governing them effectively. Audience This book should be read by legal scholars, lawyers, judges, legal and information technology researchers, cybersecurity experts, computer and software engineers, and students of law and technology. Regulators, policymakers, international trade specialists, and business executives should read it as well.